Russula quercina, a new species of Russula subsect. Integroidinae (Russulaceae, Russulales) from the Quercus mongolica forest in Heilongjiang Province, China - Zhou, Ji-Jiang; Xie, Meng-Le; Li, Guo-Jie; Song, Jia; Abdulla, Diliyar; Xing, Peng-Jie; Li, Yu; Ji, Rui-Qing; Zhang, Zhong-Hui (Phytotaxa, 2022)
Russula quercina sp. nov. (sect. Polychromidia, subsect. Integroidinae) from a Quercus mongolica forest in Northeast China is described. This new species is recognized by its coral pink and glabrous pileus, slightly yellowish context, yellow basidiospore print, and abundant cystidia in stipitipellis and pileipellis. The morphological characteristics are illustrated in detail and are compared with morphologically similar species, R. integriformis, and R. laeta. Russula quercina identification is supported by molecular phylogenetic analyses based on the internal transcribed spacer regions (ITS) in the ribosomal DNA.